2018
DOI: 10.1111/sifp.12073
|View full text |Cite
|
Sign up to set email alerts
|

Cash Transfers, Early Marriage, and Fertility in Malawi and Zambia

Abstract: There is increasing interest in the ability of cash transfers to facilitate safe transitions to adulthood in low‐income settings; however, evidence from scaled‐up government programming demonstrating this potential is scarce. Using two experimental evaluations of unconditional cash transfers targeted to ultra‐poor and labor‐constrained households over approximately three years in Malawi and Zambia, we examine whether cash transfers delayed early marriage and pregnancy among youth aged 14 to 21 years at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…A recent review paper, reviewing 23 programmes addressing child marriage implemented between 1973 and 2009, found that programmes offering incentives (such as cash transfers or school material) and those attempting to empower girls (by providing information and skills and changing attitudes and practices) can be effective at reducing rates of child marriage [ 41 ]. However, the limited evidence available examining the ability of government cash transfer programmes in Africa to reduce early marriage is mixed at best and more research is needed [ 42 , 43 ]. While the aforementioned research investigates programmes to prevent child marriage, little research is done about what kind of programmes work to help children who are already married.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review paper, reviewing 23 programmes addressing child marriage implemented between 1973 and 2009, found that programmes offering incentives (such as cash transfers or school material) and those attempting to empower girls (by providing information and skills and changing attitudes and practices) can be effective at reducing rates of child marriage [ 41 ]. However, the limited evidence available examining the ability of government cash transfer programmes in Africa to reduce early marriage is mixed at best and more research is needed [ 42 , 43 ]. While the aforementioned research investigates programmes to prevent child marriage, little research is done about what kind of programmes work to help children who are already married.…”
Section: Discussionmentioning
confidence: 99%
“…However these protective impacts are not replicated in all contexts (Dake et al. 2018; Handa, Peterman, et al. 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, evidence from the region on both government and nongovernmental cash transfer programs (including conditional and unconditional programs) demonstrates that these programs have in some cases reduced IPV and delayed sexual debut, pregnancy, and marriage, as well as reduced HIV risks among adolescent girls (Baird et al 2010, Baird et al 2012Cluver et al 2013;Handa et al 2014;Palermo, Handa, et al 2016;Hoddinott and Mekasha 2017;Pettifor et al 2016). However these protective impacts are not replicated in all contexts (Dake et al 2018;Handa, Peterman, et al 2015). Moreover, some of these impacts may evaporate after transfers stop, as a study looking at longer term effects shows (Baird et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study backs up research from Ethiopia that found that a woman's educational degree is a strong predictor of early marriage [46,47]. Moreover, other studies conducted in Malawi [42] and Western Uganda [42] revealed that women's education level was an independent predictor of early marriage [20,48]. This might be due to the fact that education helps people to know about their rights and enables them to make informed decisions when it comes to marriage [3,49,50].…”
Section: Discussionmentioning
confidence: 66%